1977
DOI: 10.1364/ao.16.001591
|View full text |Cite
|
Sign up to set email alerts
|

Coronagraphic technique to infer the nature of the Skylab particulate environment

Abstract: Photographs taken with the High Altitude Observatory's White Light Coronagraph (Skylab experiment SO52) are shown to contain information on the sizes and velocities of contaminant particulates around Skylab. Sizes as small as 5 microm (radius) are derived for particles as far away as 200 m from the spacecraft. The random error in the size derivation is about 30%, and no particle larger than 120 microm was observed. Transverse velocities are determined to within 0.08 m sec(-1) and radial velocities to within 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Those particles were associated with expendables from Skylab, and they could be correlated to times when the astronauts were "active" (as opposed to sleeping) or when "water dumps" occurred. From densitometer scans of the bright streaks in the ATM coronagraph frames, Schuerman et al (1977) were able to determine the velocity components (less than 10 meters/sec) and the distribution of radii (5 to 100 microns) for particles that were within 200 meters of the telescope. They concluded that direct (forward) scattering of sunlight by particles larger than a few microns in radius could account for the irradiance seen in the contaminated Skylab coronagraph images.…”
Section: Discussionmentioning
confidence: 99%
“…Those particles were associated with expendables from Skylab, and they could be correlated to times when the astronauts were "active" (as opposed to sleeping) or when "water dumps" occurred. From densitometer scans of the bright streaks in the ATM coronagraph frames, Schuerman et al (1977) were able to determine the velocity components (less than 10 meters/sec) and the distribution of radii (5 to 100 microns) for particles that were within 200 meters of the telescope. They concluded that direct (forward) scattering of sunlight by particles larger than a few microns in radius could account for the irradiance seen in the contaminated Skylab coronagraph images.…”
Section: Discussionmentioning
confidence: 99%
“…They are related by (ISSR), Carl Maag (JPL) and a future STS mission to obmethod uses a long -focal then register as out -of -focus obtained from the diameter aL = fA , (1) where f is the focal length of the system and A is the aperture of the objective.…”
Section: Distance Determinationmentioning
confidence: 99%
“…Video and coronographic measurements were undertaken on Skylab in 1973. 8,9 Stereo visible cameras were flown as part of the Induced Environment Contamination Monitor ͑IECM͒ diagnostic pallet on the shuttle. 10 The infrared telescope on SpaceLab 2 detected particles in its field of view.…”
Section: Introductionmentioning
confidence: 99%